Multiprocessor platform for partitioned real‐time systems. (13th May 2016) - Pérez Tijero, Héctor; Aldea Rivas, Mario; Medina Ortega, Daniel
Summary: Two current trends in the real‐time and embedded systems are the multiprocessor architectures and the partitioning technology that enables several isolated applications with different criticality levels to share the same computer. This paper presents a real‐time platform for multiprocessor and partitioned systems, in which communication requirements are also considered. The paper describes the adaptation of MaRTE OS (a monoprocessor real‐time operating system) to the XtratuM hypervisor for the multiprocessor Intel x86 architecture. This adaptation makes two contributions to ease the development process of future mixed‐criticality applications: firstly, it integrates the hypervisor technology and the fully partitioned scheduling in a multiprocessor environment, and secondly, it provides the basis to interconnect partitioned and non‐partitioned applications via a homogeneous communication subsystem. Copyright © 2016 John Wiley & Sons, Ltd.